2021
DOI: 10.1111/jfpp.16145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roasting pre‐treatment of two grafted pine nuts ( Pinus koraiensis ) on yield, color, chemical compositions, antioxidant activity, and oxidative stability of the oil

Abstract: In this study, pine nut kernels from two grafted species: Pinus koraiensis (PK) and Pinus sylvestris var. (PKS) were roasted (130, 150, 180℃ for 10, 20, 30 min) to investigate the effect of roasting pre-treatment on chemical components, antioxidant activity, and oxidative stability of oils prepared from kernels. Increased temperature or time was found to cause a significant increase in oil yield, color, total phenolic content (TPC), carotenoid, and browning index (BI) of oils compared to unroasted samples. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The highest BI for WSO (0.412) and BSO (0.275) was observed by DAR and IRR at 200°C for 15 min, respectively. A similar change in BI was recorded for the oil obtained from thermally processed pine nuts (An et al, 2022). DAR and IRR time showed a greater significant effect than the temperature on BI of SO (Table S1a,b; p ≤ .005).…”
Section: Resultssupporting
confidence: 77%
“…The highest BI for WSO (0.412) and BSO (0.275) was observed by DAR and IRR at 200°C for 15 min, respectively. A similar change in BI was recorded for the oil obtained from thermally processed pine nuts (An et al, 2022). DAR and IRR time showed a greater significant effect than the temperature on BI of SO (Table S1a,b; p ≤ .005).…”
Section: Resultssupporting
confidence: 77%
“…Kovats retention indices (RI) of C 5 ~C25 nalkanes were calculated by chromatographic scanning under the same chromatographic conditions as the sample determination, followed by comparison with corresponding literature values. RI was calculated according to the following formula (2). Where: R t(i) , R t(n) , and R t(n+1) are the retention time of the unknown substance to be measured, and the n-alkanes containing n and n + 1 carbon atoms, respectively.…”
Section: Determination Of Volatile Flavor Substancesmentioning
confidence: 99%
“…As one of China's traditional edible oils, Korean pine seed oil (KPSO) boasts high levels of unsaturated fatty acids, vitamin E, beta-sitosterol (a plant sterol), and other potent antioxidants [1]. With a smoke point typically exceeding 180 • C (356 • F), KPSO exhibits remarkable stability during high temperature cooking methods such as stir-frying and deep-frying, minimizing the risk of smoke generation and scorching [2]. By incorporating natural wax into KPSO to form an oil gel, not only can the thermal stability of KPSO be further enhanced but also additional nutritional benefits can be provided [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that volatile profiles of pine nuts were significantly influenced by species (PK and PKS) and roasting conditions, and moderate roasting conditions (150°C for 20 min) could obtain more suitable quality characteristics (Adelina et al, 2020). Roasting treatment could make bioactive compounds leach into pine kernel oil, thereby improving oil yield, nutritional value and oxidative stability (An et al, 2021). Heat‐treatment time and temperature could change protein structure (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Roasting treatment could make bioactive compounds leach into pine kernel oil, thereby improving oil yield, nutritional value and oxidative stability (An et al, 2021). Heat-treatment time and temperature could change protein structure .…”
mentioning
confidence: 99%